Polityka konkurencji Unii Europejskiej w warunkach globalizacji gospodarki światowej - Latoszek, Ewa; Kłos, Agnieszka (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
The aim of this article is to present the essence of competition policy and its implementation in the European Union in the context of ongoing globalization of the world economy. The paper will present selected factors that stimulate the process of globalization, main objectives and tools supporting the functioning of the EU internal market, and the place of the European Commission as a body that enforces compliance with the rules of competition by companies and the Member States.